Strategies for Coping With Stress Used by Nurses in Poland and Belarus During the COVID-19 Pandemic - Kowalczuk, Krystyna; Shpakou, Andrei; Hermanowicz, Justyna M.; Krajewska-Kułak, Elzbieta; Sobolewski, Marek (Frontiers in Psychiatry, 2022)
Introduction: Stress is an inseparable element of nurses' work and also the cause of well-being disorders and various diseases. An appropriate coping strategy can reduce the impact of stress and mitigate its negative consequences. The Covid-19 pandemic was a source of enormous additional stress for nurses. In Poland and Belarus, the authorities took a completely different approach to fighting the pandemic. Aim: The purpose of this study was to investigate and compare how nurses in Poland and Belarus cope with stress during the Covid-19 pandemic. Material and method: The cross-sectional study was conducted among 284 nurses working in hospital in Bialystok, Poland (158) and in Grodno, Belarus (126). Mini-Cope inventory - the polish adaptation of Carver’s BriefCope was used for measuring coping with stress. Results: Only 17.5% of Belarusian nurses were tested for the presence of the virus and only 4.8% were infected, while in Poland it was 50.6% and 31.0% respectively. The most frequent used coping strategies were active strategies (active coping, planning) and the least-used were avoidance strategies (behavioral disengagement, substance use) in both countries. Polish nurses significantly more often than Belorussian used support-seeking/emotion-oriented strategies, as well as avoidance strategies. No differences were found for active coping strategies between the both groups. Contact with a patient infected did not influence the choice of stress coping strategies by nurses in both countries. Staying in quarantine or home isolation favored more active coping strategies. Taking a SARS-CoV-2 test did not statistically differentiate the choice of coping strategies in the Belarusian group. In the Polish group, nurses with a positive SARS-CoV-2 test result used both instrumental support and emotional support strategies less frequently. Infection did not statistically differentiated coping in Polish group. Conclusions: Polish and Belorussian nurses used similar strategies to cope with stress in the face of the Covid-19 pandemic. The social and demographic factors differentiated the coping strategies to a greater extent than the approach of authorities to the pandemic. Being in quarantine or home isolation favored the use of active coping strategies among Belorussian nurses. Polish nurses were more likely to turn to religion after being quarantined.